Shaping the Microglia in Retinal Degenerative Diseases Using Stem Cell Therapy: Practice and Prospects - Jin, Ni; Sha, Weiwei; Gao, Lixiong (Frontiers in Cell and Developmental Biology, 2021)
Retinal degenerative disease (RDD) refers to a group of diseases with retinal degeneration that cause vision loss and affect people’s daily lives. Various therapies have been proposed, among which stem cell therapy (SCT) holds great promise for the treatment of RDDs. Microglia are immune cells in the retina that have two activation phenotypes, namely, pro-inflammatory M1 and anti-inflammatory M2 phenotypes. These cells play an important role in the pathological progression of RDDs, especially in terms of retinal inflammation. Recent studies have extensively investigated the therapeutic potential of SCT in treating RDDs, including the immunomodulatory effects targeting microglia. In this review, we substantially summarized the characteristics of RDDs and microglia, discussed the microglial changes and phenotypic transformation of M1 microglia to M2 microglia after SCT, and proposed future directions for SCT in treating RDDs.